Wi-Fi received signal strength-based hyperbolic location estimation for indoor positioning systems - Narzullaev A.; Selamat M.H.; Sharif K.Y.; Muminov Z. (Inderscience Enterprises Ltd., 2024)
Indexed by SCOPUS/ERA